A PRACTICAL THEOLOGY OF WORK AND LEADERSHIP - Bates, Paul K. (My University, 2020)
This dissertation seeks to comprehend and respond to deterioration in what is considered to be a very significant foundation of human flourishing—a sense of vigour, vitality, purpose and meaningfulness at work. The term flourishing in the workplace is offered both in the sense that work satisfies a person’s economic needs (fair pay and job security) and in the sense that it satisfies a person’s deeper sense of vocation, of Spirit- led calling. This dissertation responds to the concern that the postmodern workplace, for a number of reasons, inhibits a person's ability to flourish. Yet, this dissertation will argue, there is a deep thirst for meaningfulness in our daily endeavour. We are settling for less. From the research conducted, this dissertation develops an approach to practices of leadership that bring about deep purpose to be derived from our work. Further, this dissertation develops an approach for ministry that might facilitate these Spirit-led practices. The premise is that leadership that is self-centred must be transformed into leadership that is other-centered. Leadership is conceived as critical to the nurturing of human flourishing, ultimately affecting our behaviours beyond the workplace. There are two dimensions to the qualitative research designed for this dissertation, as described by the questionnaires completed by research respondents. The first is to seek an unaided broad response to questions regarding peoples’ sense of purpose, self-esteem, value, and self-actualization. The second is to seek an understanding of the degree to which such responses are shaped by a person's sense of faith. Beyond these dimensions, the research explores the extent to which respondents engage with a minister or spiritual counsellor.
Note this dissertation is in partial fulfilment of the requirements for the degree of Doctor of Practical Theology
Keywords: work; leadership; meaningfulness